2022
DOI: 10.1155/2022/6096981
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Infectious Laryngotracheitis Infection and Associated Risk Factors in Chickens in Northwestern Ethiopia

Abstract: Infectious laryngotracheitis (ILT) is a disease of high economic consequence to the poultry sector. Gallid herpesvirus 1 (GaHV-1), a.k.a infectious laryngotracheitis virus (ILTV), under the genus Iltovirus, and the family Herpesviridae, is the agent responsible for the disease. Despite the clinical signs on the field suggestive of ILT, it has long been considered nonexistent and a disease of no concern in Ethiopia. A cross-sectional study was conducted from November 2020 to June 2021 in three selected zones of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
1
3
1
Order By: Relevance
“…The present finding agrees with the finding of Mohamad Inkyas et al, (2014) who reported 17.33% from Chitta gong districts of Bangladish and Tesfaye et al, (2019) with finding of 19.4% from central and southern parts of Ethiopia. On the other hand, the current finding was lower than the reports of Owoade et al, (2006), Roba et al, (2020; Salhi et al, (2021); Johnson et al, (2004); Madsen et al, (2013); Derksen et al, (2018), Birhan et al, (2022); who reported a seroprevalence of 20%; 59.1%; 54.7%, 56.25%, 57.1%, 49%; 45% in Nigeria, Ada'a district of Oromia region in Ethiopia, in Algeria; in Delmarva, Maryland, and Northwestern part of Ethiopia respectively. This variation might be due to vaccination in those developed countries where ILT vaccination is utilized.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…The present finding agrees with the finding of Mohamad Inkyas et al, (2014) who reported 17.33% from Chitta gong districts of Bangladish and Tesfaye et al, (2019) with finding of 19.4% from central and southern parts of Ethiopia. On the other hand, the current finding was lower than the reports of Owoade et al, (2006), Roba et al, (2020; Salhi et al, (2021); Johnson et al, (2004); Madsen et al, (2013); Derksen et al, (2018), Birhan et al, (2022); who reported a seroprevalence of 20%; 59.1%; 54.7%, 56.25%, 57.1%, 49%; 45% in Nigeria, Ada'a district of Oromia region in Ethiopia, in Algeria; in Delmarva, Maryland, and Northwestern part of Ethiopia respectively. This variation might be due to vaccination in those developed countries where ILT vaccination is utilized.…”
Section: Discussioncontrasting
confidence: 93%
“…Among the host-related risk factors, only breed showed a significant association with seroprevalence (p<0.05). Sasso breed chickens had 9.68 times more likely in the odds of seropositivity as compared to local breed and Bovans exotic breeds (AOR: 9.68, 95%CI: 1.96 -47.78) This study was in line with finding of Birhan et al, (2022) who reported that local chickens had a 62% reduction in the odds of seropositivity as compared to exotic breed. Studies have shown that local breeds of chickens have better environmental adaptability and disease resistance traits than exotic breeds (Wong et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations